Cyber Jihad: Waging War Through Social Media to Defend Islamic Values - Yusi Mardiah Cahyani; Muthoifin (Solo International Collaboration and Publication of Social Sciences and Humanities, 2024)
In the modern digital era, the phenomenon of cyber jihad has emerged as a strategy used by various groups and individuals to wage war through social media to defend Islamic values. This research aims to investigate the phenomenon of cyber jihad and how this activity aims to strengthen and defend Islamic values in existing challenges and ideological rivalries. This research method analyses the content of various social media platforms to spread jihad narratives, mobilise support, and promote ideological agendas. An interdisciplinary approach is used to understand the complexity of this phenomenon, including the dimensions of religion, politics, and information technology. The data was collected through literature studies, online observations, and interviews with relevant experts. The analysis identified behavioural patterns, communication strategies, and social impacts of cyber jihad activities. The findings of this study are expected to provide deeper insights into the role of social media in championing Islamic values and its implications for global social dynamics and security.